First molecular genotyping of voltage gated sodium channel alleles in Culex quinquefasciatus populations in Malaysia - Low, V.L.; Chen, C.D.; Lim, P.E.; Lee, H.L.; Tan, T.K.; Lim, Y.A.L.; Sofian-Azirun, Mohd (2013)
A nationwide investigation was performed to detect the presence of 1014 mutation(s) in voltage gated sodium channel (kdr) gene of Culex quinquefasciatus from 14 residential areas across 13 states and a federal territory in Malaysia. Molecular genotyping of kdr mutation was performed via a modified three tubes allele-specific-polymerase chain reaction (AS-PCR) and direct sequencing of kdr gene. Based on the results of AS-PCR, homozygous susceptible (SS) genotype was found in nine out of 14 populations with 38 individuals from a total sample size of 140. Heterozygous (RS) genotype was most predominant (99 individuals) and distributed across all study sites. Homozygous resistance (RR) genotype was detected in Perak (one individual) and Selangor (two individuals). The resistance kdr allele frequencies ranged from 0.1 to 0.55, with the highest being detected in Cx. quinquefasciatus population from Selangor. This study has documented the first field-evolved instance of 1014F mutation in Malaysian mosquitoes and the findings of this study could be utilized in the implementation of strategic measures in vector control programs in Malaysia. (C) 2013 Elsevier Inc. All rights reserved.